Estimated burden of cardiovascular disease and value-based price range for evolocumab in a high-risk, secondary-prevention population in the US payer context. (3rd June 2017) - Toth, Peter P.; Danese, Mark; Villa, Guillermo; Qian, Yi; Beaubrun, Anne; Lira, Armando; Jansen, Jeroen P.
Abstract: Aim: To estimate real-world cardiovascular disease (CVD) burden and value-based price range of evolocumab for a US-context, high-risk, secondary-prevention population. Materials and methods: Burden of CVD was assessed using the UK-based Clinical Practice Research Datalink (CPRD) in order to capture complete CV burden including CV mortality. Patients on standard of care (SOC; high-intensity statins) in CPRD were selected based on eligibility criteria of FOURIER, a phase 3 CV outcomes trial of evolocumab, and categorized into four cohorts: high-risk prevalent atherosclerotic CVD (ASCVD) cohort ( n  = 1448), acute coronary syndrome (ACS) ( n  = 602), ischemic stroke (IS) ( n  = 151), and heart failure (HF) ( n  = 291) incident cohorts. The value-based price range for evolocumab was assessed using a previously published economic model. The model incorporated CPRD CV event rates and considered CV event reduction rate ratios per 1 mmol/L reduction in low-density lipoprotein-cholesterol (LDL-C) from a meta-analysis of statin trials by the Cholesterol Treatment Trialists Collaboration (CTTC), i.e. CTTC relationship. Results: Multiple-event rates of composite CV events (ACS, IS, or coronary revascularization) per 100 patient-years were 12.3 for the high-risk prevalent ASCVD cohort, and 25.7, 13.3, and 23.3, respectively, for incident ACS, IS, and HF cohorts. Approximately one-half (42%) of the high-risk ASCVD patients with a new CV event during follow-up had a subsequent CV event. Combining these real-world event rates and the CTTC relationship in the economic model, the value-based price range (credible interval) under a willingness-to-pay threshold of $150, 000/quality-adjusted life-year gained for evolocumab was $11, 990 ($9, 341–$14, 833) to $16, 856 ($12, 903–$20, 678) in ASCVD patients with baseline LDL-C levels ≥70 mg/dL and ≥100 mg/dL, respectively. Conclusion: Real-world CVD burden is substantial. Using the observed CVD burden in CPRD and the CTTC relationship, the cost-effectiveness analysis showed that, accounting for uncertainties, the expected value-based price for evolocumab is higher than its current annual cost, as long as the payer discount off list price is greater than 20%.